IMPACT OF COMPUTER-AIDED DESIGN AND DRAFTING ON STUDENTS’ ATTITUDE AND PERFORMANCE IN TECHNICAL DRAWING IN UNITY COLLEGES IN PORT HARCOURT - SIMINIALAYI, Leticia Iyarubo, FOMSI, Esther Fabiawari (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The study investigated the impact of Computer-Aided Design and Drafting (CADD) on students’ attitude and performance in Technical drawing in Unity Colleges in Port Harcourt using quasi-experimental and descriptive survey designs. Samples of eighty (80) Technical drawing students from the two unity colleges in Port Harcourt were drawn from a population of 228 students. Two research questions were answered and two hypotheses tested at 0.05 level of significance. Instruments used for data collection were Technical Drawing Achievement Test (TDAT) to determine students’ performance and Technical Drawing Structured Questionnaire (TDSQ) used to measure students’ attitude towards Computer-Aided Design and Drafting usage. Data collected were analyzed using SPSS (Mean and Standard Deviation to answer research questions, while ANCOVA and Independent t-test were used to test the hypotheses). The findings revealed among others; that CADD had significant impact on students’ performance in Technical drawing, and also positively influenced the attitude of the students. Recommendations include among others; that the Nigerian Educational Research & Development Council (NERDC) should design a curriculum that will enforced the incorporation of modern technology software such as the CADD in the teaching and learning process in Secondary Schools in every subject areas as this will help to promote the learning outcome and thus bringing about positive change towards students’ attitude in the different subject areas.